MANAGEMENT OF TECHNOLOGY: THE MISSING LINK - Alina Shamsuddin (2014)
The management of technology (MoT) is one of the disciplines which is widely but vaguely known, let alone truly understood and implemented. Therefore it is perhaps not surprising that many organizations are unaware that they are already managing the technology utilized in their respective companies to deliver their products or services in a competent and effective manner! To comprehend and command the powerful tool of MoT will enable enhanced performance of an organization, by mobilizing its talents, potentials and assets in a unified effort towards maximum productivity. Naturally this little book cannot claim to cover every aspect of MoT, but it does paint a general picture of MoT’s roles and functions in today’s competitive business world, as with a broad paint brush. It defines technology from the perspectives of MoT, resource-based theory (RBV) as well as performance management (PM). A case study is included to better illustrate the adoption and adaptation of MoT in a company. One may not transform into an MoT guru by reading the book, but one can surely hope to be enlightened, albeit a little, on the WHATs and the HOWs of MoT.